Boardroom diversity and financial performance in Palestinian banks and insurers - Aladdin Dwekat; Abdulmalik Taweel; Ali Salameh (Discover Sustainability)
Abstract This study examines the impact of board diversity—precisely age, nationality, and experience—on the financial performance of 13 Palestinian banks and insurance companies listed on the Palestine Stock Exchange (PEX) from 2011 to 2022. Using a comprehensive panel data approach and controlling for endogeneity with a two-step system Generalized Method of Moments (GMM) estimator, the analysis explores how diverse board characteristics influence financial outcomes measured by ROA and ROE. Unlike previous studies focused mainly on developed markets or gender diversity, this research offers new insights into the role of board diversity in emerging economies, particularly in the Middle Eastern context. The results reveal that while age diversity negatively impacts firm performance, experience diversity positively correlates, underscoring the importance of industry-specific expertise in financial governance. Nationality diversity, however, exhibits no significant effect, suggesting that foreign representation may introduce complexity without necessarily enhancing performance. These findings contribute to Agency Theory, Upper Echelons Theory, and Resource Dependence Theory, offering practical recommendations for regulators and firms in developing markets to optimise board composition. This study expands the discourse on board diversity by highlighting the nuanced effects of specific diversity dimensions in the financial sector, providing valuable insights for governance practices in similar economic environments.